1996
DOI: 10.1136/bjo.80.6.515
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of automated visual field examination in children between 5 and 8 years of age.

Abstract: Aims-To investigate how young children develop the ability to undergo a visual field evaluation using regular automated perimetry. Methods-The study included 42 normal girls aged 5, 6, 7, and 8 years. Twelve locations in the 15 degrees eccentricity were tested in one eye, using an Octopus 2000R perimeter with a two level strategy. False positive and false negative catch trials were presented. The examination was performed three times in succession. Before the examination procedure, a specially designed program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 3 publications
3
26
0
Order By: Relevance
“…The few available systematic studies concerning automated visual field testing in children mainly agree that 8 years of age is about the cut-off age for obtaining reliable results. As Tschopp et al (1995Tschopp et al ( , 1998aTschopp et al ( , 1998bTschopp et al ( , 1999 and Safran et al (1996) have shown, younger children can be tested after a familiarization phase, but this limits clinical practicability. In our study, it was noted that children up to 8 years of age performed better with the ramp stimulus (CLIP) than with a staircase strategy (fast threshold), but many of our results were still found to be non-reliable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The few available systematic studies concerning automated visual field testing in children mainly agree that 8 years of age is about the cut-off age for obtaining reliable results. As Tschopp et al (1995Tschopp et al ( , 1998aTschopp et al ( , 1998bTschopp et al ( , 1999 and Safran et al (1996) have shown, younger children can be tested after a familiarization phase, but this limits clinical practicability. In our study, it was noted that children up to 8 years of age performed better with the ramp stimulus (CLIP) than with a staircase strategy (fast threshold), but many of our results were still found to be non-reliable.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have examined children in their habitual school environment after training (Tschopp et al 1995(Tschopp et al , 1998a(Tschopp et al , 1998b(Tschopp et al , 1999Safran et al 1996), others have used paid volunteers (Morales & Brown 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When examining their results further, mean sensitivity values are variable until 11-12 years. Safran et al, 28 also using the Octopus perimeter, used a static testing strategy on the central 15 , and found good reliability in 8-year-olds. They noted that a training programme improved results, especially in the younger children.…”
Section: Feasibility Of Testing Childrenmentioning
confidence: 99%
“…The shortest test was obtained using SITA Fast with stimulus size III (3.3 min). Safran et al [9] examined girls aged 5–8 years, using the Octopus 2000R perimeter with a custom ‘two-level’ strategy that tested 12 locations at 15° eccentricity. Mean test duration for one eye was 13 min in 5-year-olds and 7 min in 8-year-olds.…”
Section: Discussionmentioning
confidence: 99%